Enantioselective Construction of Vicinal Tetrasubstituted Stereocenters by the Mannich Reaction of Silyl Ketene Imines with Isatin‐Derived Ketimines. (7th November 2014) - Zhao, Jiannan; Fang, Bing; Luo, Weiwei; Hao, Xiaoyu; Liu, Xiaohua; Lin, Lili; Feng, Xiaoming
Abstract: A highly enantioselective Mannich reaction of silyl ketene imines with isatin‐derived ketimines has been realized by using a chiral N, N′ ‐dioxide/Zn II catalyst. A variety of β‐amino nitriles containing congested vicinal tetrasubstituted stereocenters were obtained with excellent outcomes (up to 98 % yield, >19:1 d.r. and 99 % ee ). Based on the experimental investigations, a possible transition state has been proposed to explain the origin of the asymmetric induction. Abstract : Quartäres Gedränge : Die Titelreaktion mit dem Zink(II)‐Komplex eines chiralen N, N′ ‐Dioxids als Katalysator liefert eine Reihe von β‐Aminonitrilen mit vicinalen tetrasubstituierten Stereozentren. Ein Übergangszustand wird vorgeschlagen, der die asymmetrische Induktion erklären könnte. Boc= tert ‐Butoxycarbonyl, TBS= tert ‐Butyldimethylsilyl, Tf=Trifluormethansulfonyl.